The effect of neonatal nursing care on clinical symptoms and intestinal flora of children with acute diarrhea - Wang, Linxue (Cellular and Molecular Biology, 2022)
Nursing care for infants in the neonatal intensive care unit (NICU) is very complex and may affect the function of the infant microbiome. Several factors inherent in staying in the intensive care unit, such as the use of antibiotics, non-antibiotic drug interventions, nutritional components, and various invasive procedures, including surgery, are associated with disruption of the host microbiota. Therefore, the NICU nurse needs to consider effect factors on the microbial growth and the role that the microbiome may play in causing disease since admission to the NICU. In this study, we describe the association between the gut microbiome and neonatal nursing care at the NICU and the cellular and molecular factors affecting the intestinal flora of children with acute diarrhea.